The Survey on Adolescents' Cognition, Attitude, and Behavior of Using Analgesics: Take Sichuan and Chongqing as an Example - Yin, Lian; Wang, Kun; Zhang, Tingran; Liu, Hengxu; Li, Yinghong; Luo, Jiong (Frontiers in Public Health, 2022)
Objectives To explore the current situation of knowledge, attitude, and behavior about the correct use of analgesics among adolescents in Western Sichuan and Chongqing and its related factors and to provide a reference for health promotion schools to promote correct medication education and relevant policy-making. Methods A questionnaire survey was conducted among senior high school students in Sichuan and Chongqing by stratified random sampling. A total of 48 classes were surveyed and 2,280 valid questionnaires were obtained. Descriptive analysis, mean value comparison, and multiple regression analysis were conducted for the data using SPSS17.0 statistical analysis software. Results (1) It showed that 65.5% of the students used methods other than drugs to deal with pain, 52.9% of the students took analgesics prescribed by doctors, more than 60% of the students got information about pain treatment from medical professionals or their families members, 71.6% of the students read the use label when using drugs, and only about 20% of the students knew the dosage and side effects of analgesics. (2) The higher the grade, the higher the proportion of students who often take analgesics prescribed by doctors, the higher the proportion of students who use methods other than drugs to relieve pain, the higher the proportion of students who read the label of analgesics, and the more information sources are introduced by family members. The better the knowledge, attitude, efficacy, and accomplishment of using analgesics, the better the behavior of using analgesics correctly. (3) Students who had taken analgesics provided by their family or friends and who had taken anti-inflammatory analgesics did not perform well in the correct use of analgesics. Conclusion The key factors that influence the correct drug use behavior of middle school students are their correct drug use literacy, efficacy, attitude, and reading of analgesics. Therefore, schools should strengthen cooperation with pharmacists and encourage the promotion of parent-child education activities of correct drug use.